Post-Tuberculosis Pulmonary Impairment: Prevalence, Functional Limitation, and Quality of Life in Adult Patients - Islam, Mohammad Shafiqul; Khan, Mohammed Asaduzzaman; Hossain, Md Afzal; Akter, Rahana; Md Shahen (Journal of Dhaka National Medical College & Hospital, 2026)
Background: Tuberculosis (TB) remains a major global health burden, and despite effective treatment, many survivors develop post-tuberculosis pulmonary impairment (PTB-PI). This condition leads to chronic respiratory symptoms, reduced lung function, and poor quality of life. The lack of standardized post-TB care results in neglected morbidity. Objectives: To determine the prevalence, patterns, functional limitations, and quality of life among adult patients with post-tuberculosis pulmonary impairment. Materials and Methods: This cross-sectional study was conducted it Dhaka National Medical College, Department of Pulmonology, from January to December 2024, including 156 adults with completed TB treatment. Data were collected through questionnaires, spirometry, and standardized scales (mMRC, SF-36). Descriptive and inferential statistics were performed using SPSS v23. Ethical approval was obtained from the Institutional Review Board, and written informed consent was secured from all participants. Result: Among 156 patients, mean age was 43.2 years with male predominance (62.8%). Pulmonary impairment was highly prevalent (73.7%), primarily obstructive (36.5%) and restrictive (28.8%) patterns. Most patients (69.2%) reported dispend, with 27.5% experiencing severe functional limitation (mMRC 3-4). Smoking was a major risk factor, with 82.3% of smokers/ex-smokers impaired versus 55.0% of non-smokers. Quality of life was most affected in physical functioning (only 23.1% good) and energy levels (32.0% poor). Conclusion: This study confirms PTB-PI is highly prevalent and debilitating, necessitating integrated post-TB care within national health programs. J Dhaka National Med. Coll. Hos. 2025; 31 (02): 40-45